Quadratic Algebraic Integers - Ali, Hassan S. (Libyan Journal of Science &Technology, 2022)
Certain the map from the set of all Quadratic Algebraic Integers into Certain the map from the set of all Quadratic Algebraic Integers into is proved a ring isomorphism.